Parotidectomy-related facial nerve lesions: proposal for a modified Sunnybrook Facial Grading System - Márcia Gonçalves e Silva Targino da COSTA; Péricles de Andrade MARANHÃO-FILHO; Izabella Costa SANTOS; Ronir Raggio LUIZ; Maurice Borges VINCENT (Arquivos de Neuro-Psiquiatria)
ABSTRACT Facial nerve injury, affecting mainly the marginal mandibular branch, is the most frequent neurologic complication from parotidectomy. Objective To test a modified Sunnybrook Facial Grading System as a new tool to assess the facial nerve function following parotidectomy, emphasizing the marginal mandibular branch. Methods We reviewed the medical records of 73 post-parotidectomy patients (40 female, 18-84 years old, mean age 53.2 years) with facial nerve sparing, referred to the Department of Physical Therapy. All patients had parotid neoplasms or advanced skin cancer, and were followed by the principal author between 2006 and 2014. Results The muscles innervated by the marginal mandibular branch were the most frequently affected (72.6%), particularly in patients undergoing neck dissection (p = 0.023). The voluntary movement scores obtained with the modified system were significantly lower compared with the original version (p < 0.001). The best and worst scores were observed in patients with benign parotid tumors and skin cancer, respectively. Patients requiring neck dissection (p = 0.031) and resection of other structures (p = 0.021) had the lowest scores, evidenced only with the modified version. Patients with malignant tumors had significantly worse ratings, regardless of the Sunnybrook system version. The post-physiotherapy analysis involved 50 patients. The worst facial rehabilitation outcomes were related to the marginal mandibular branch function. Conclusion The modified Sunnybrook Facial Grading System improved the marginal mandibular branch assessment, preserving the evaluation of other facial nerve branches.